Intraoperative Ultrasound for Bowel Deep Infiltrating Endometriosis: A Preliminary Report. (29th September 2020) - Puppo, Andrea; Olearo, Elena; Gattolin, Andrea; Rimonda, Roberto; Novelli, Antonia; Ceccaroni, Marcello
Abstract : The decision to perform either conservative surgery or segmental bowel resection for bowel deep infiltrating endometriosis (DIE) is made intraoperatively, after a preoperative assessment, based on the nodule's features. We introduce a technique to evaluate DIE bowel nodules using laparoscopic intraoperative ultrasound (US) during laparoscopic radical treatment of 9 cases of DIE invading the bowel. Once the bowel lesion was isolated, an intraoperative 12–4‐MHz US transducer was placed on the surface of the nodules to study their US features and to gain measurements. Deep infiltrating endometriosis nodules appear at intraoperative US as hypoechoic elliptical lesions with a clear definition of margins and the depth of infiltration of the rectal wall.